Data Resource: Vascular Risk in Adult New Zealanders (VARIANZ) datasets - Mehta, Suneela; Jackson, Rod; Exeter, Daniel J; Wu, Billy P; Wells, Sue; Kerr, Andrew J (International Journal of Population Data Science, 2019)
Introduction The Vascular Risk in Adult New Zealanders (VARIANZ) datasets contain a range of routinely-collected New Zealand health data relevant to cardiovascular disease (CVD) and related conditions. The datasets enable exploration of cardiovascular-related treatment, service utilisation, outcomes and prognosis. Processes Each dataset is constructed by anonymised individual-level linkage of eight national administrative health databases to identify all New Zealand adults aged 20 years and older who have recorded contact with publicly-funded New Zealand health services during a given year from 2006 onwards, when data quality is considered sufficient. Data contents Individual-level data for each VARIANZ dataset includes variables covering demography, dispensing of cardiovascular disease (CVD) preventive medications, prior hospitalisations for atherosclerotic CVD, heart failure, atrial fibrillation, diabetes and five-year risk of a fatal or non-fatal CVD event for those without prior CVD. If required, VARIANZ datasets can be individually linked to follow-up national routinely collected health data in subsequent years, including all-cause mortality events, fatal and non-fatal CVD events and dispensing of cardiovascular medications, to create VARIANZ longitudinal cohorts. Bespoke linkage can also be undertaken to include other national and regional administrative health data such as non-CVD related hospitalisations, or to identify a subset of the VARIANZ datasets based on specific health contacts such as CVD-related hospitalisations only. The New Zealand routinely-collected health databases used to construct the VARIANZ datasets do not capture primary care diagnostic classifications or certain CVD risk factor data such as smoking status, blood pressure or lipid profiles. Conclusions The Vascular Risk in Adult New Zealanders (VARIANZ) datasets capture the majority of the New Zealand population in a given year and are available for any year from 2006 onwards. VARIANZ data can be used to explore a range of research questions regarding management, outcomes and prognosis for CVD.